Challenging the knowledge‐transfer orthodoxy: Knowledge co‐construction in technology‐enhanced learning for children with autism. (April 2017) - Guldberg, Karen; Parsons, Sarah; Porayska‐Pomsta, Kaśka; Keay‐Bright, Wendy
Abstract : Experimental intervention studies constitute the current dominant research designs in the autism education field. Such designs are based on a 'knowledge‐transfer' model of evidence‐based practice in which research is conducted by researchers, and is then 'transferred' to practitioners to enable them to implement evidence‐based interventions. While these research designs contribute important knowledge, they lead to a gap between what the research evidence may prescribe and what happens in practice, with a concomitant disparity between the priorities of researchers and practitioners. This paper discusses findings from the ESRC‐funded 'SHAPE' project, which adopted a different model of evidence‐based practice, focusing on knowledge co‐construction. Pupils ( N  =   8), teachers ( N  =   10), a speech and language therapist and a parent in three different school communities investigated creative ways in which children's social communication skills could be enhanced through technology use. Through a participatory methodology, digital stories were used as a method to enable engagement with the practical realities of the classroom and empower practitioners to construct and share their own authentic narratives. Participants articulated precise knowledge about the learning opportunities afforded to them and their pupils through quality interactions that were mediated by the technologies, as evidenced through digital stories. The SHAPE project shows that it is feasible to develop methodologies that enable genuine knowledge co‐construction with school practitioners, parents and pupils. Such co‐construction could offer realistic opportunities for pedagogical emancipation and innovation in evidence‐based practice as an alternative to the currently dominant and narrow model of knowledge transfer.